Financing for development : proposals from business and civil society - Herman, Barry (United Nations University Press TokyoJP, 2001)
Addresses the question of how to boost the financing of development. Covers topics ranging from micro credit to large-scale project finance; from gender and poverty to bridging the digital divide; from local to global environments for investment; from domestic to international taxation; from trade expansion to debt relief; and, from official development assistance to reform of the United Nations.